2020
DOI: 10.30935/cedtech/8400
|View full text |Cite
|
Sign up to set email alerts
|

How Postgraduate Students Use Video to Help Them Learn

Abstract: Purpose of the study: The object of this paper is to explore the literature in order to discover on what conditions a video-mediated form of instruction can be a learning instrument, the one that enhances teaching, increases the potential of improving learners' performance and leads to a change in students' knowledge and behaviours. Methodology: This exploration is literature based and involves a critical discussion of articles on video-based instruction and video pedagogies. Main findings: Video-based forms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Likewise, the design and production of videos enable updating the educational field activities (Cakiroglu & Yilmaz, 2017;Iskru & Schulz, 2020;Vera et al, 2015). In the physics course, the use of the videos facilitated the learning process about the phenomenon of free fall, increased motivation, and improved the participation of the students (Vera et al, 2015).…”
Section: Use Of Technology In the Educational Process About Physicsmentioning
confidence: 99%
“…Likewise, the design and production of videos enable updating the educational field activities (Cakiroglu & Yilmaz, 2017;Iskru & Schulz, 2020;Vera et al, 2015). In the physics course, the use of the videos facilitated the learning process about the phenomenon of free fall, increased motivation, and improved the participation of the students (Vera et al, 2015).…”
Section: Use Of Technology In the Educational Process About Physicsmentioning
confidence: 99%
“…Some post-graduation courses have worked towards that end in order to encourage the use and production of educational technologies, enhance different cognitive functions, improve the teaching-learning process, and, therefore, contribute with the formation of future professors. Among the technologies explored, the educational videos, which have been frequently used during classes, stand out, since they enhance learning by explaining theoretical concepts and using images that stimulate the imagination (7) .…”
Section: Production and Use Of Educational Technologies In Nursing Po...mentioning
confidence: 99%
“…Based on the perspective according to which concepts or subjects must be taught in many different ways to activate different intelligences or their combinations (5,7) , disciplines from the nursing post-graduation course from the Universidade Federal de Pernambuco (Nursing PGP -UFPE) have provided professors with the experience, production, use, and application of the new educational technologies through active methodologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Video is gaining a firm foothold in the educational landscape (Iskru and Schulz, 2020), and research into mobile video technology in education has revealed wide-ranging benefits in The use of video to maximise cooking skills terms of meeting the needs of the learning requirements of the digital native (Wishart, 2016). Prensky (2009) contends that digital natives are used to receiving information at speed, preferring to parallel and multi-task; therefore, the portability of video may offer this option of learning for some students (Lim, 2006).…”
Section: Video and The Learning Environmentmentioning
confidence: 99%